A comprehensive analysis of the microbial communities of healthy and diseased marine macroalgae and the detection of known and potential bacterial pathogens - Zozaya-Valdes, Enrique; Egan, Suhelen; Thomas, Torsten (Frontiers in Microbiology, 2015)
Microorganisms are increasingly being recognized as the causative agents in the diseases of marine higher organisms, such as corals, sponges and macroalgae. Delisea pulchra is a common, temperate red macroalga, which suffers from a bleaching disease. Two bacterial strains, Nautella italica R11 and Phaeobacter gallaeciensis LSS9, have been shown in vitro to cause bleaching symptoms, but previous work has failed to detect them during a natural bleaching event. To provide a link between in vitro observations and natural occurrences of the disease, we employ here deep-sequencing of the 16S rRNA gene to comprehensively analyze the community composition of healthy and diseased D. pulchra samples from two separate locations. We observed operational taxonomic units (OTUs) with 100% identity and coverage to the 16S RNA gene sequence of both in vitro pathogens, but only the OTU with similarity to strain LSS9 showed a statistically significant higher abundance in diseased samples. Our analysis also reveals the existence of other bacterial groups within the families Rhodobacteraceae and Flavobacteriaceae that strongly contribute to difference between diseased and healthy samples and thus these groups potentially contain novel macroalgal pathogens and/or saprophytes. Together our results provide evidence for the ecological relevance of one kind of in vitro pathogen, but also highlight the possibility that multiple opportunistic pathogens are involved in the bleaching disease of D. pulchra.